2014
DOI: 10.18632/oncotarget.2063
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine inhibits angiogenesis and tumor growth by targeting the VEGFR-2/PI3K/mTOR pathway in ovarian cancer xenografts

Abstract: Thioridazine, a member of the phenothiazine family, is a powerful anti-anxiety and anti-psychotic drug. It can also suppress the growth of several types of tumor in vitro. In the current study, we evaluated the direct anti-tumor and anti-angiogenic effects of thioridazine in vivo. The injection of thioridazine into human ovarian tumor xenografts in nude mice significantly inhibited tumor growth by ~fivefold, and also decreased tumor vascularity. In addition, thioridazine inhibited the phosphorylation of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Consistent with the expression of HIF1α, VEGF was downregulated. Inhibition of angiogenesis may result in anticancer efficacy (30). Overexpression or hyper-activation of Nrf2 may participate in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the expression of HIF1α, VEGF was downregulated. Inhibition of angiogenesis may result in anticancer efficacy (30). Overexpression or hyper-activation of Nrf2 may participate in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been particularly successful with non-steroidal antiinflammatory drugs (NSAIDs) and antidiabetics such as metformin (1,2). Phenothiazine-derived antipsychotic drugs such as thioridazine and chlorpromazine exhibit anticarcinogenic activity in several different cancer cell lines (39). More recent studies have demonstrated that penfluridol, another antipsychotic drug, also inhibits breast and pancreatic cancer cell growth (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Thioridazine (Thio), a phenothiazine derivative, is a piperidine antipsychotic drug that was recently found to inhibit cancer cell growth. [6][7][8] Doxorubicin (Dox), an anthracycline antibiotic, is one of the most widely applied anticancer drugs for various malignancies, including breast, prostate, and colon cancers. [9][10][11][12] However, serious side effects, such as the dose-dependent cardiotoxicity, myelosuppression, and nephrotoxicity, markedly limit its clinical use.…”
Section: Introductionmentioning
confidence: 99%